Thermal energy and charge currents in multi-terminal nanorings - Kramer, Tobias; Kreisbeck, Christoph; Riha, Christian; Chiatti, Olivio; Buchholz, Sven S.; Wieck, Andreas D.; Reuter, Dirk; Fischer, Saskia F. (AIP Advances)

Electric field distribution and exciton recombination line shape in GaAs - Schuster, J; Kim, T Y; Batke, E; Reuter, Dirk; Wieck, A D (Materials Research Express)

Photoluminescence excitation spectroscopy of excited states of an asymmetric cubic GaN/Al0.25Ga0.75N double quantum well grown by molecular beam epitaxy - Wecker, Tobias; Callsen, Gordon; Hoffmann, Axel; Reuter, Dirk; As, Donat Josef (Japanese Journal of Applied Physics)

Stabilizing nuclear spins around semiconductor electrons via the interplay of optical coherent population trapping and dynamic nuclear polarization - Onur, A. R.; de Jong, J. P.; O'Shea, D.; Reuter, Dirk; Wieck, A. D.; van der Wal, C. H. (Physical Review B)

Heat flow, transport and fluctuations in etched semiconductor quantum wire structures - Riha, Christian; Chiatti, Olivio; Buchholz, Sven S.; Reuter, Dirk; Wieck, Andreas D.; Fischer, Saskia F. (physica status solidi (a))

Reconstruction of nuclear quadrupole interaction in (In,Ga)As/GaAs quantum dots observed by transmission electron microscopy - Sokolov, P. S.; Petrov, M. Yu.; Mehrtens, T.; Müller-Caspary, K.; Rosenauer, A.; Reuter, Dirk; Wieck, A. D. (Physical Review B)

DevOps for network function virtualisation: an architectural approach - Karl, Holger; Dräxler, Sevil; Peuster, Manuel; Galis, Alex; Bredel, Michael; Ramos, Aurora; Martrat, Josep; Siddiqui, Muhammad Shuaib; van Rossem, Steven; Tavernier, Wouter; Xilouris, George (Transactions on Emerging Telecommunications Technologies)
The Service Programming and Orchestration for Virtualised Software Networks (SONATA) project targets both the flexible programmability of software networks and the optimisation of their deployments by means of integrating Development and Operations in order to accelerate industry adoption of software networks and reduce time-to-market for networked services. SONATA supports network function chaining and orchestration, making service platforms modular and easier to customise to the needs of different service providers, and introduces a specialised Development and Operations model for supporting developers.

DCT²Gen: A traffic generator for data centers - Wette, Philip; Karl, Holger (Computer Communications)

Composition of SDN applications: Options/challenges for real implementations - Schwabe, Arne; A. Aranda-Gutierrez, Pedro; Karl, Holger (Proceedings of the 2016 Applied Networking Research Workshop, ANRW 2016, Berlin, Germany, July 16, 2016)

Reusability of software-defined networking applications: A runtime, multi-controller approach - Doriguzzi Corin, Roberto; A. Aranda-Gutierrez, Pedro; Rojas, Elisa; Karl, Holger; Salvadori, Elio (12th International Conference on Network and Service Management, CNSM 2016, Montreal, QC, Canada, October 31 - Nov. 4, 2016)

Understand Your Chains: Towards Performance Profile-Based Network Service Management - Peuster, Manuel; Karl, Holger (Fifth European Workshop on Software-Defined Networks, EWSDN 2016, Den Haag, The Netherlands, October 10-11, 2016)
Allocating resources to virtualized network functions and services to meet service level agreements is a challenging task for NFV management and orchestration systems. This becomes even more challenging when agile development methodologies, like DevOps, are applied. In such scenarios, management and orchestration systems are continuously facing new versions of functions and services which makes it hard to decide how much resources have to be allocated to them to provide the expected service performance. One solution for this problem is to support resource allocation decisions with performance behavior information obtained by profiling techniques applied to such network functions and services. In this position paper, we analyze and discuss the components needed to generate such performance behavior information within the NFV DevOps workflow. We also outline research questions that identify open issues and missing pieces for a fully integrated NFV profiling solution. Further, we introduce a novel profiling mechanism that is able to profile virtualized network functions and entire network service chains under different resource constraints before they are deployed on production infrastructure.

Demonstrating on-demand cell switching with a two-layer mobile network testbed - Peuster, Manuel; Karl, Holger; Enrico Redondi, Alessandro; Capone, Antonio (IEEE Conference on Computer Communications Workshops, INFOCOM Workshops 2016, San Francisco, CA, USA, April 10-14, 2016)
Traditional cellular networks are forced to remain active regardless of the actual amount of traffic that is currently produced/requested, with a clear waste of energy. Two-layer mobile networks with separated signalling and data layers have been recently proposed for energy savings in future implementations. These networks are able to switch off unneeded data cells completely while maintaining full coverage with their signalling cells, thus saving energy. In this demonstration, we showcase a testbed that uses Wi-Fi access points to emulate small cells of the data layer and a publicly available cellular connection as the signalling layer. We use off-the-shelf Android smartphones with an ad-hoc networking management module and a MultiPath TCP-enabled kernel to manage the Wi-Fi and cellular interfaces simultaneously. The testbed is used to demonstrate the general feasibility of this layered architecture and to facilitate experiments with network-wide resource optimization.

E-State: Distributed state management in elastic network function deployments - Peuster, Manuel; Karl, Holger (IEEE NetSoft Conference and Workshops, NetSoft 2016, Seoul, South Korea, June 6-10, 2016)
Elastic deployments of virtualized network functions~(VNF) can automatically scale the amount of used resources in relation to their workload. This is often done by starting new VNF instances or stopping old ones. A problem of these scale operations is that most network functions are stateful and their internal state is not automatically migrated when traffic is redistributed in the deployment. As a result, mechanisms are needed to exchange or migrate internal network function state between VNF instances. This paper presents a state management framework that creates a logically distributed state store on top of elastically deployed virtual network functions. We also introduce a novel programming model that provides both a local and a global view of the state to each VNF instance. We discuss the integration of our framework into existing network function virtualization architectures and compare the performance of our prototype to a centralized and a distributed state store solution.

Joint real-time scheduling and interference coordination for wireless factory automation - Auroux, Sébastien; Parruca, Donald; Karl, Holger (27th IEEE Annual International Symposium on Personal, Indoor, and Mobile Radio Communications, PIMRC 2016, Valencia, Spain, September 4-8, 2016)

MeDICINE: Rapid Prototyping of Production-Ready Network Services in Multi-PoP Environments - Peuster, Manuel; Karl, Holger; van Rossem, Steven (IEEE Conference on Network Function Virtualization and Software Defined Networks (NFV-SDN))
Virtualized network services consisting of multiple individual network functions are already today deployed across multiple sites, so called multi-PoP (points of presence) environments. This allows to improve service performance by optimizing its placement in the network. But prototyping and testing of these complex distributed software systems becomes extremely challenging. The reason is that not only the network service as such has to be tested but also its integration with management and orchestration systems. Existing solutions, like simulators, basic network emulators, or local cloud testbeds, do not support all aspects of these tasks. To this end, we introduce MeDICINE, a novel NFV prototyping platform that is able to execute production-ready network functions, provided as software containers, in an emulated multi-PoP environment. These network functions can be controlled by any third-party management and orchestration system that connects to our platform through standard interfaces. Based on this, a developer can use our platform to prototype and test complex network services in a realistic environment running on his laptop.

Understanding Loyalty Program Effectiveness: Managing Target and Bystander Effects - Steinhoff, Lena; Palmatier, Robert W. (Journal of the Academy of Marketing Science)

Fabrication of fully undercut ZnO-based photonic crystal membranes with 3D optical confinement - Hoffmann, Sandro Phil; Albert, Maximilian; Meier, Cedrik (Superlattices and Microstructures)

Formate als Sackgassen: Handlungsempfehlungen - Bohl, Benjamin W.; Berndt, Axel; Senft, Björn (Konferenzabstracts der 3. Tagung des Verbands "Digital Humanities im deutschsprachigen Raum e. V.")

Design Thinking als Methode in den Digital Humanities. Optionen interdisziplinären, forschenden Lehrens und Lernens - Greulich, Markus; Karthaus, Nicola; Oberthür, Simon; Schmidt, Ariane; Senft, Björn; Stog, Kristina (Konferenzabstracts der 45. Jahrestagung der Deutschen Gesellschaft für Hochschuldidaktik)

Von implizitem Wissen zu nachhaltigen Systemanforderungen - Meise, Bianca; Mexin, Yevgen; Schloots, Franziska M.; Senft, Björn; Wawilow, Anastasia; Engels, Gregor; Meister, Dorothee M.; Müller-Lietzkow, Jörg; Szwillus, Gerd (Tagungsband der Forschungsdaten in den Geisteswissenschaften (FORGE))

Interdisziplinäre Forschung als Basis nachhaltiger Entscheidungsprozesse in der Softwareentwicklung - Meise, Bianca; Mexin, Yevgen; Schloots, Franziska M.; Senft, Björn; Wawilow, Anastasia (Konferenzband: 1. interdisziplinären Konferenz zur Zukunft der Wertschöpfung)

Auf dem Weg zu einer experimentellen und evidenzbasierten Softwareentwicklung in den Digital Humanities - Senft, Björn; Oberthür, Simon (Konferenzabstracts der 3. Tagung des Verbands "Digital Humanities im deutschsprachigen Raum e. V.")

Software Processes Management by Method Engineering with MESP - Fazal-Baqaie, Masud; Engels, Gregor (Managing Software Process Evolution)

Gerechtigkeit in flexiblen Arbeits- und Managementprozessen - Engels, Gregor; W. Maier, Günter; Ötting, Sonja; Steffen, Eckhard; Teetz, Alexander (Zukunft der Arbeit: Eine praxisnahe Betrachtung)

Model-Driven Software Modernization: Concept-Based Engineering of Situation-Specific Methods - Grieger, Marvin

The Service Award Paradox - Cramer, C; Böhm, E; Eggert, A (Proceedings of the 45th European Marketing Academy (EMAC) Conference)

Understanding Service Awards: Exploit the Bright Side, Avoid the Dark Side - Cramer, C; Böhm, E; Eggert, A (2016 AMA Winter Marketing Educators' Conference Proceeding)

Shedding Light on Outcome-Based Contracts: Benefits and Risks from the Buyers’ and Sellers’ Perspective - Böhm, E; Backhaus, C; Eggert, A; Pitsis, T (2016 AMA Winter Marketing Educators' Conference Proceedings)

Model-Integrating Microservices: A Vision Paper - Derakhshanmanesh , Mahdi; Grieger, Marvin (Gemeinsamer Tagungsband der Workshops der Tagung Software Engineering 2016 (SE 2016))

Mathe – nein danke? Interesse, Beliefs und Lernstrategien im Mathematikstudium bei Grundschullehramtsstudierenden mit Pflichtfach - Kolter, Jana; Liebendörfer, Michael; Schukajlow, Stanislaw (Lehren und Lernen von Mathematik in der Studieneingangsphase)

Research in University Mathematics Education: The khdm - Biehler, Rolf; Hochmuth, Reinhard; Rück, Hans-Georg; Göller, Robin; Hoppenbrock, Axel; Liebendörfer, Michael; Püschl, Juliane (EMS Newsletter)

Abschreiben - ein Problem in mathematischen Lehrveranstaltungen? - Liebendörfer, Michael; Göller, Robin (Hanse-Kolloquium zur Hochschuldidaktik der Mathematik 2014 Beiträge zum gleichnamigen Symposium am 7. & 8. November 2014 an der Westfälischen Wilhelms-Universität Münster)

Eine alternative Einstiegsvorlesung in die Fachmathematik – Konzept und Auswirkungen - Göller, Robin; Liebendörfer, Michael (Beiträge zum Mathematikunterricht 2016)
Keywords: _tablet; Abschreiben

Abschreiben von Übungsaufgaben in traditionellen und innovativen Mathematikvorlesungen - Liebendörfer, Michael; Göller, Robin (Mitteilungen der Deutschen Mathematiker-Vereinigung)
Keywords: _tablet; Abschreiben

Evidence of Singlet-Triplet Crossing in Photoluminescence of Positively Charged Excitons in GaAs Quantum Wells - Bryja, L.; Wójs, A.; Jadczak, J.; Misiewicz, J.; Płochocka, P.; Potemski, M.; Reuter, Dirk; Wieck, A. (Acta Physica Polonica A)

From Localised to Ballistic Excitons in GaAs Quantum Wells - Pulizzi, F.; Christianen, P.C.M.; Maan, J.C.; Eshlaghi, S.; Reuter, Dirk; Wieck, A.D. (Acta Physica Polonica A)

Multiobjective Model Predictive Control of an Industrial Laundry - Peitz, Sebastian; Gräler, Manuel; Henke, Christian; Molo, Mirko Hessel-von; Dellnitz, Michael; Trächtler, Ansgar (Procedia Technology)
In a wide range of applications, it is desirable to optimally control a system with respect to concurrent, potentially competing goals. This gives rise to a multiobjective optimal control problem where, instead of computing a single optimal solution, the set of optimal compromises, the so-called Pareto set, has to be approximated. When it is not possible to compute the entire control trajectory in advance, for instance due to uncertainties or unforeseeable events, model predictive control methods can be applied to control the system during operation in real time. In this article, we present an algorithm for the solution of multiobjective model predictive control problems. In an offline scenario, it can be used to compute the entire set of optimal compromises whereas in a real time scenario, one optimal compromise is computed according to an operator's preference. The results are illustrated using the example of an industrial laundry. A logistics model of the laundry is developed and then utilized in the optimization routine. Results are presented for an offline as well as an online scenario.

From Localised to Ballistic Excitons in GaAs Quantum Wells - Pulizzi, F.; Christianen, P.C.M.; Maan, J.C.; Eshlaghi, S.; Reuter, Dirk; Wieck, A.D. (Acta Physica Polonica A)

Improved Automatic Computation of Hessian Matrix Spectral Bounds - Schulze Darup, Moritz; Mönnigmann, Martin (SIAM Journal on Scientific Computing)

An Economic Theory of 'Destabilization War' - Gries, Thomas; Haake, Claus-Jochen
While Islamic State is the most present example, it is a fact that in many places around the globe, throughout history initially small groups have tried to challenge and destabilize or even overthrow governments by means of terrorist and guerrilla strategies. Therefore, we answer two questions. Why does a small group of insurgents believe it can overthrow the government by turning violent, even if the government is clearly superior? And how does a conflict develop into terrorism, a guerilla war, or a major conventional civil war, or is resolved peacefully? We develop a formal model for rebels and government and derive optimal choices. Further, we focus on three elements as important ingredients of a "destabilization war". All three of these - large random events, time preference (which we relate to ideology), and choice of duration of fight - are rarely considered in formal conflict theory. We can answer the above two questions using game theory analysis. First, insurgents rise up because they hope to destabilize through permanent challenging attacks. In this context, large randomness is an important ally of rebels. While each individual attack may have a low impact, at some point a large random event could lead to success. Hence, the duration of activities is a constitutive element of this kind of armed conflict. Patience (low time preference), which may reflect rebels' degree of ideological motivation, is crucial. Second, the mode of warfare or the conflict resolutions that develop are generally path-dependent and conditioned on the full set of options (including compromise). Various conditions (level of funding, ease of recruitment, access to weapons) influence different modes of warfare or a peaceful compromise in a complex way.
Keywords: terrorism; civil war; conflict duration; game theory; stochastic process; ideology

The Project SEEL – Basic information about the context - Beutner, Marc; Schneider, J (Sounds and Audios in E-learning scenarios. Results and Discussions on the basic of the SEEL project)

The strcture of the SEEL Project - Beutner, Marc; Schneider, J (Sounds and Audios in E-learning scenarios. Results and Discussions on the basis of the SEEl project)

Situation of visual impaired in Germany - Beutner, Marc; Schneider, J (Sounds and Audios in E-learning scenarios. Results and Discussions on the basis of the SEEl project)

Quasi-Experimental Design concerning learning with sounds in education - Beutner, Marc (Sounds and Audios in E-learning scenarios. Results and Discussions on the basis of the SEEl project)

The general structure of the SEEL Teacher Training Course - Beutner, Marc; Schneider, J (Sounds and Audios in E-learning scenarios. Results and Discussions on the basis of the SEEl project)

Insights in the evaluation results of the SEEL Project - Beutner, Marc (Sounds and Audios in E-learning scenarios. Results and Discussions on the basis of the SEEl project)

Anglistentag 2015 Paderborn: Proceedings

Religion im zeitgenössischen britischen Drama - Tönnies, Merle (Religion und Kultur)

The Use of Comic Effects in Memoirs of British Asian Adolescence: Twenty-First Century Writers Looking Back at the 1970s and 1980s - Tönnies, Merle (Anglistik. International Journal of English Studies)

The Duality of Page and Stage: Constructing Lyrical Voices in Contemporary British Poetry Written for Performance - Tönnies, Merle; Brüning, Joana; Sand, Andrea (Zeitschrift für Anglistik und Amerikanistik)

Memory, Dementia and Narrative Identity in Alice Munro’s ‘The Bear Came Over the Mountain’ - Strauß, Sara (Traces of Aging: Old Age and Memory in Contemporary Narrative)

The Making of English Popular Culture. ed. by John Storey - Flotmann-Scholz, Christina (Journal for the Study of British Cultures)

Die literarische Kommunikationsspirale: Strukturelle Wechselwirkungen zwischen literarischem Text und Rezeption in der angelsächsischen Kinder- und Jugendliteratur des späten 20./ frühen 21. Jahrhunderts. by Uta Woiwod - Flotmann-Scholz, Christina (Anglistik: International Journal of English Studies)

Oedipal Murders and Nostalgic Ressurections: The Victorians in Historical Middlebrow Fiction, 1914-1959. by Caterina Maria Grasl - Flotmann-Scholz, Christina (Literaturwissenschaftliches Jahrbuch)

Smartphone und Tablet – Medienpädagogische und technische Grundlagen, Potential für den Deutschunterricht und Beispiele - Herzig, Bardo; Martin, Alexander; Klar, Tilman-Mathies (Deutsch Digital. Band 1 Theorie)

Quantum Correlations from the Conditional Statistics of Incomplete Data - Sperling, J.; Bartley, Tim; Donati, G.; Barbieri, M.; Jin, X.-M.; Datta, A.; Vogel, W.; Walmsley, I. A. (Physical Review Letters)

Quantum enhanced estimation of optical detector efficiencies - Barbieri, Marco; Datta, Animesh; Bartley, Tim; Jin, Xian-Min; Kolthammer, W. Steven; Walmsley, Ian A. (Quantum Measurements and Quantum Metrology)
Abstract Quantum mechanics establishes the ultimate limit to the scaling of the precision on any parameter, by identifying optimal probe states and measurements. While this paradigm is, at least in principle, adequate for the metrology of quantum channels involving the estimation of phase and loss parameters, we show that estimating the loss parameters associated with a quantum channel and a realistic quantum detector are fundamentally different. While Fock states are provably optimal for the former, we identify a crossover in the nature of the optimal probe state for estimating detector imperfections as a function of the loss parameter using Fisher information as a benchmark. We provide theoretical results for on-off and homodyne detectors, the most widely used detectors in quantum photonics technologies, when using Fock states and coherent states as probes.

Monitoring and debugging using an SDK for NFV-powered telecom applications - v. Rossem, S.; Tavernier, W.; Peuster, Manuel; Colle, D.; Pickavet, M.; Demeester, P. (Proc. IEEE Conference on Network Function Virtualization and Software Defined Network (NFV-SDN), Demo Track)

Shape-Dependent Transmittable Tangential Force of Wire Bond Tools - Althoff, Simon; Meyer, Tobias; Unger, Andreas; Sextro, Walter; Eacock, Florian (IEEE 66th Electronic Components and Technology Conference)
Wire bonding has been an established packaging technology for decades. When introducing copper as wire material for high power applications, adaptations to the bonding process and to machines became necessary. Here, challenges occur due to the stiffer wire material and changing oxide layers on the contact partners. To achieve sufficient process stability, a clean bond area is required, which can only be achieved with high shear stresses in the contact partners surfaces. These necessitate high normal forces to plastically deform the wire and substrate. To achieve such high stresses in the contact area, the bonding tool needs to be able to transmit the needed tangential forces to the top side of the wire. The wire itself performs a shear movement and transmits the force into the contact area to clean the contaminant and oxide layers and to level the desired bond surfaces. The main function of the tool is to transmit these forces. If the bond tool can only transmit low forces in the direction of excitation, the parameter space for a stable bond process is severely restricted. Here, a modeling approach to estimate how well different tool shapes meet the demand of transmitting high tangential forces is presented. The model depends on wire deformation and thus on the ultrasonic softening effect.
Keywords: finite element simulation; wire bonding; tool geometry

Kupferbondverbindungen intelligent herstellen - Brökelmann, Michael; Unger, Andreas; Meyer, Tobias; Althoff, Simon; Sextro, Walter; Hunstig, Matthias; Biermann, Florian; Guth, Karsten (wt-online)
Leistungshalbleitermodule werden leistungsfähiger, effizienter, kompakter und haltbarer Ziel dieses Innovationsprojekts des Spitzenclusters „it’s OWL – Intelligente Technische Systeme OstWestfalen-Lippe“ ist die Entwicklung von selbstoptimierenden Verfahren, um unter variablen Produktionsbedingungen zuverlässige Kupferbondverbindungen herstellen zu können. Die Ultraschall-Drahtbondmaschine erhält die Fähigkeit, sich automatisch an veränderte Bedingungen anzupassen. Hierzu wird der gesamte Prozess der Ultraschall-Verbindungsbildung modelliert und neueste Verfahren der Selbstoptimierung angewandt. Die Evaluierung erfolgt anhand eines Prototypen in Form einer modifizierten Bondmaschine. Intelligent production of heavy copper wire bonds It is the aim of this innovation-project to develop a self-optimization system for ultrasonic copper wire bonding. It is part of the leading edge cluster “it’s OWL”. The bonding machine will be able to react autonomously to changing boundary conditions to ensure constant and reliable bonding results. For this, the hole bonding process is modeled in great detail and newest self-optimization techniques are utilized. A prototype-system incorporated in a serial machine is used for evaluation.

Transportation of dry fine powders by coordinated friction manipulation - Dunst, Paul; Sextro, Walter; Bornmann, Peter; Hemsel, Tobias; Littmann, Walter (PAMM Proc. Appl. Math. Mech. 16)
The transportation of dry fine powders is an emerging technologic task, as in biotechnology, pharmaceutical or coatings industry particle sizes of processed powders are getting smaller and smaller. Fine powders are primarily defined by the fact that adhesive and cohesive forces outweigh the weight forces. This leads to mostly unwanted agglomeration (clumping) and adhesion to surfaces, what makes it more difficult to use conventional conveyor systems (e. g. pneumatic or vibratory conveyors) for transport. A rather new method for transporting these fine powders is based on ultrasonic vibrations, which are used to reduce friction and adhesion between powder and the substrate. One very effective set-up consists of a pipe, which vibrates harmoniously in axial direction at low frequency combined with a pulsed radial high frequency vibration. The high frequency vibration accelerates the particles perpendicular to the surface of the pipe, which in average leads to lower normal and thereby smaller friction force. With coordinated friction manipulation the powder acceleration can be varied so that the powder may be greatly accelerated and only slightly decelerated in each excitation period of the low frequency axial vibration of the pipe. The amount of powder flow is adjustable by vibration amplitudes, frequencies, and pulse rate, which makes the device versatile for comparable high volume and fine dosing using one setup. Within this contribution an experimental set-up consisting of a pipe, a solenoid actuator for axial vibration and a piezoelectric actuator for the radial high frequency vibration is described. An analytical model is shown, that simulates the powder velocity. Finally, simulation results are validated by experimental data for different driving parameters such as amplitude of low frequency vibration, pipe material and inclination angle.

Effect of different oxide layers on the ultrasonic copper wire bond process - Eacock, Florian; Unger, Andreas; Eichwald, Paul; Grydin, Olexandr; Hengsbach, Florian; Althoff, Simon; Schaper, Mirko; Guth, Karsten (IEEE 66th Electronic Components and Technology Conference)
Ultrasonic heavy wire bonding is a commonly used technology to conduct electrical devices in power electronics. In order to facilitate powerful solutions combined with an increased efficiency, involving a material change from aluminum to copper wire as conductor material takes place in recent years. Due to the material related properties, copper wire bonding requires significant higher bond processing parameters such as bond force and ultrasonic power compared to aluminum which can lead to damages or a failure of the bonded component. Therefore, a profound knowledge of the processes prevailing during wire bonding is essential to optimize the application of the copper wires and consequently to achieve the demands on quality and reliability. The behavior of different natural surface oxides of aluminum and copper are assumed to be one reason for the deviation in the required bond parameters. Accordingly, the impact of differently pre-treated substrates surfaces on which the bonding is applied were investigated in this study. First, all conditions investigated (as-received, oxidefree, AlOx and the CuOx) were characterized by utilizing scanning electron microscopy, energy dispersive X-ray spectroscopy, focused ion beam microscopy and atomic force microscopy. In addition, hardness tests were performed as well as perthometer measurements. Afterwards, a 500 $μ$ m copper wire was bonded on the generated surfaces investigated. In consideration of the roughness, shear test of various bond times and microscopic images were evaluated. Finally, the results were compared and discussed. Overall, the current study indicates that an Al-oxide layer is beneficial for welding process in Cu wire bonding. On the contrary, the Cu-oxide is detrimental and leads to a delayed welding of the joining parts. Based on the obtained results, it can be expected that due to an ideal set of Al-oxide layers, lower optimal bond parameters can used to reach high bond strength with good reliability properties.
Keywords: Ultrasonic copper wire bonding; Al-oxide; Cuoxide; oxide-free; roughness; morphology

Micro Wear Modeling in Copper Wire Wedge Bonding - Eichwald, Paul; Unger, Andreas; Eacock, Florian; Althoff, Simon; Sextro, Walter; Guth, Karsten; Brökelmann, Michael (IEEE CPMT Symposium Japan, 2016)
Ultrasonic wire bonding is a common technology for connecting electrodes of electronic components like power modules. Nowadays, bond connections are often made of copper instead of aluminum due to its thermal and mechanical assets. One of the main cost factors in the wire bonding process is the acquisition cost of consumables such as bonding tools. For copper wire bonding tool lifetime is much lower than for aluminium bonding. This paper presents a micro wear model for wedge/wedge bonding tools that was validated by observing wear patterns with a scanning electron microscope. The wear coefficient is determined in long-term bonding tests. The application of Fleischer´s wear approach incorporating frictional power to a finite element simulation of the bonding processes is used to shift element nodes depending on the rising frictional power for finite element modeling. The presented simulation method can be used to take tool wear into consideration for creating tools with increased lifetime. This enables the production of reliable bond connections using heavy as well as thin wire of any material. The paper discusses the predominant influences of wear on the main tool functions and their changes over tool life. Furthermore, the influence of the tool groove angle on the tool wear was investigated. One of the main results is that the wear is largest during the last phase of each bonding process, when the contact area between tool and wire is largest.

Modeling of Complex Redundancy in Technical Systems with Bayesian Networks - Kaul, Thorben; Meyer, Tobias; Sextro, Walter (Proceedings of the Third European Conference of the Prognostics and Health Management Society 2016)
Redundancy is a common approach to improve system reliability, availability and safety in technical systems. It is achieved by adding functionally equivalent elements that enable the system to remain operational even though one or more of those elements fail. This paper begins with an overview on the various terminologies and methods for redundancy concepts that can be modeled sufficiently using established reliability analysis methods. However, these approaches yield very complex system models, which limits their applicability. In current research, Bayesian Networks (BNs), especially Dynamic Bayesian Networks (DBNs) have been successfully used for reliability analysis because of their benefits in modeling complex systems and in representing multi-state variables. However, these approaches lack appropriate methods to model all commonly used redundancy concepts. To overcome this limitation, three different modeling approaches based on BNs and DBNs are described in this paper. Addressing those approaches, the benefits and limitations of BNs and DBNs for modeling reliability of redundant technical systems are discussed and evaluated.

Aspects of Flexible Viscoelastic Suspension Modeling for Frictional Rolling Contact Analysis using ADAMS - Kohl, Sergej; Sextro, Walter; Schulze, Sebastian (The 2nd International Conference on Automotive Innovation and Green Energy Vehicle (AiGEV 2016), Cyberjaya, Malaysia, 2016.)
Tire-wheel assembly is the only connection between road and vehicle. Contacting directly with road within postcard size of contact area, it is mounted and guided by the suspension system. Therefore kinematics and compliances of suspension system greatly influence the frictional coupling of tire tread elements and road surface asperities by affecting pressure and sliding velocity distribution in the contact zone. This study emphasizes the development of a numerical methodology for frictional rolling contact analysis with focus on interaction of suspension system dynamics and tire-road contact using ADAMS. For this purpose a comprehensive flexible multibody system of the multi-link rear suspension is established, where both flexible and rigid bodies are modeled to allow large displacements with included elastic effects. To meet accuracy requirements for the high frequency applications, such as road excitations, the amplitude- and frequency-dependency of rubber-metal bushings is included. Furthermore the proposed flexible viscoelastic suspension model is enhanced by a Flexible Ring Tire Model (FTire), which describes a 3D tire dynamic response and covers any road excitations by tread submodel connected to road surface model. Concerning the verification and validation procedure numerous experiments are carried out to confirm the validity and the accuracy of both the developed submodels and the entire model. The devised approach makes it possible to investigate the influence of suspension system design on dynamical rolling contact and to evaluate tire tread wear. Therefore it can be a useful tool to predict frictional power distribution within the contact area under more realistic conditions.
Keywords: Kinematics and compliances; flexible viscoelastic suspension model; frictional rolling contact analysis; frictional power distribution.

Condition Monitoring of Bearing Damage in Electromechanical Drive Systems by Using Motor Current Signals of Electric Motors: A Benchmark Data Set for Data-Driven Classification - Lessmeier, Christian; Kimotho, James Kuria; Zimmer, Detmar; Sextro, Walter (European Conference of the Prognostics and Health Management Society)
This paper presents a benchmark data set for condition monitoring of rolling bearings in combination with an extensive description of the corresponding bearing damage, the data set generation by experiments and results of datadriven classifications used as a diagnostic method. The diagnostic method uses the motor current signal of an electromechanical drive system for bearing diagnostic. The advantage of this approach in general is that no additional sensors are required, as current measurements can be performed in existing frequency inverters. This will help to reduce the cost of future condition monitoring systems. A particular novelty of the present approach is the monitoring of damage in external bearings which are installed in the drive system but outside the electric motor. Nevertheless, the motor current signal is used as input for the detection of the damage. Moreover, a wide distribution of bearing damage is considered for the benchmark data set. The results of the classifications show that the motor current signal can be used to identify and classify bearing damage within the drive system. However, the classification accuracy is still low compared to classifications based on vibration signals. Further, dependency on properties of those bearing damage that were used for the generation of training data are observed, because training with data of artificially generated and real bearing damages lead to different accuracies. Altogether a verified and systematically generated data set is presented and published online for further research

Reliable Manufacturing of Heavy Copper Wire Bonds Using Online Parameter Adaptation - Meyer , Tobias; Unger, Andreas; Althoff, Simon; Sextro, Walter; Brökelmann, Michael; Hunstig, Matthias; Guth, Karsten (IEEE 66th Electronic Components and Technology Conference)
Usage of copper wire bonds allows to push power boundaries imposed by aluminum wire bonds. Copper allows higher electrical, thermal and mechanical loads than aluminum, which currently is the most commonly used material in heavy wire bonding. This is the main driving factor for increased usage of copper in high power applications such as wind turbines, locomotives or electric vehicles. At the same time, usage of copper also increases tool wear and reduces the range of parameter values for a stable process, making the process more challenging. To overcome these drawbacks, parameter adaptation at runtime using self-optimization is desired. A self-optimizing system is based on system objectives that evaluate and quantify system performance. System parameters can be changed at runtime such that pre-selected objective values are reached. For adaptation of bond process parameters, model-based self-optimization is employed. Since it is based on a model of the system, the bond process was modeled. In addition to static model parameters such as wire and substrate material properties and vibration characteristics of transducer and tool, variable model inputs are process parameters. Main simulation result is bonded area in the wiresubstrate contact. This model is then used to find valid and optimal working points before operation. The working point is composed of normal force and ultrasonic voltage trajectories, which are usually determined experimentally. Instead, multiobjective optimalization is used to compute trajectories that simultaneously optimize bond quality, process duration, tool wear and probability of tool-substrate contacts. The values of these objectives are computed using the process model. At runtime, selection among pre-determined optimal working points is sufficient to prioritize individual objectives. This way, the computationally expensive process of numerically solving a multiobjective optimal control problem and the demanding high speed bonding process are separated. To evaluate to what extent the pre-defined goals of self-optimization are met, an offthe- shelf heavy wire bonding machine was modified to allow for parameter adaptation and for transmitting of measurement data at runtime. This data is received by an external computer system and evaluated to select a new working point. Then, new process parameters are sent to the modified bonding machine for use for subsequent bonds. With these components, a full self-optimizing system has been implemented.
Keywords: Self-optimization; adaptive system; bond process; copper wire

Using Adequate Reduced Models for Flexible Multibody Systems of Automotive Mechatronic Systems - Schulze, Sebastian; Sextro, Walter; Kohl, Sergej (2nd International Conference on Automotive Innovation and Green Energy Vehicle (AiGEV) Malaysia 2016)
Multibody models of mechatronic systems are usually interdisciplinary and are continuously gaining complexity, due to a growing demand for comprehensive models of systems including effects of electro mechanics, elastic bodies, contacts and friction. To be capable of simulating large models with subassemblies and contact between bodies, reduction techniques are required, which need certain experience in the choice of parameters. This publication discusses different possibilities for the modal description of structures in flexible multibody models with application to an Adaptive Frontlighting System in ADAMS. It will be shown that mode count, assembling of structures before and after modal reduction and influence of damping parameters of particular structures and subassemblies affect the behavior of the entire system. A common reduction technique for flexible structures in multibody models is the component mode synthesis, which uses a certain number of modes for description of the modal behavior of a structure. The influence of the mode count will be shown by means of different modal descriptions of one structure that contributes to a comprehensive model. Another study will prove that modal data of subassemblies and assemblies of modal reduced single structures lead to different models. The definition of damping parameters depends on the number of structures that have been added to an assembly before modal reduction and on the number of modal reduced structures. The comparison of subassemblies and the entire model to experimental data will highlight the accuracy, computational overhead, complexity of models and modeling efficiency of the comprehensive model for the frontlighting system.
Keywords: model reduction; modal description; flexible multibody systems

Validated Simulation of the Ultrasonic Wire Bonding Process - Unger, Andreas; Schemmel, Reinhard; Meyer, Tobias; Eacock, Florian; Eichwald, Paul; Althoff, Simon; Sextro, Walter; Brökelmann, Michael; Hunstig, Matthias; Guth, Karsten (Wear Modeling in Copper Wire Wedge Bonding. IEEE CPMT Symposium Japan, 2016)
To increase quality and reliability of copper wire bonds, self-optimization is a promising technique. For the implementation of self-optimization for ultrasonic heavy copper wire bonding machines, a model of stick-slip motion between tool and wire and between wire and substrate during the bonding process is essential. Investigations confirm that both of these contacts do indeed show stick-slip movement in each period oscillation. In a first step, this paper shows the importance of modeling the stick-slip effect by determining, monitoring and analyzing amplitudes and phase angles of tooltip, wire and substrate experimentally during bonding via laser measurements. In a second step, the paper presents a dynamic model which has been parameterized using an iterative numerical parameter identification method. This model includes Archard’s wear approach in order to compute the lost volume of tool tip due to wear over the entire process time. A validation of the model by comparing measured and calculated amplitudes of tool tip and wire reveals high model quality. Then it is then possible to calculate the lifetime of the tool for different process parameters, i.e. values of normal force and ultrasonic voltage.
Keywords: the Ultrasonic Wire Bonding Process

Wave interaction in photonic integrated circuits: Hybrid analytical / numerical coupled mode modeling - Hammer, Manfred (Integrated Optics: Devices, Materials, and Technologies XX)
Typical optical integrated circuits combine elements, like straight and curved waveguides, or cavities, the simulation and design of which is well established through numerical eigenproblem-solvers. It remains to predict the interaction of these modes. We address this task by a ”Hybrid” variant (HCMT) of Coupled Mode Theory. Using methods from finite-element numerics, the optical properties of a circuit are approximated by superpositions of eigen-solutions for its constituents, leading to quantitative, low-dimensional, and interpretable models in the frequency domain. Spectral scans are complemented by the direct computation of supermode properties (spectral positions and linewidths, coupling-induced phase shifts). This contribution outlines the theoretical background, and discusses briefly limitations and implementational details, with the help of an example of a 2-D coupled-resonator-optical-waveguide configuration.
Keywords: tet_topic_waveguide; tet_topic_numerics

Low-voltage DNTT-based thin-film transistors and inverters for flexible electronics - Meyers, Thorsten; Vidor, Fábio F.; Brassat, Katharina; Lindner, Jörg; Hilleringmann, Ulrich (Microelectronic Engineering)
In this article we present an integration technique for low-voltage DNTT-based TFTs for flexible electronic applications. Therefore, a high-k nanocomposite combining the flexibility of its polymericmatrix and the high permittivity of the incorporated inorganic material was used as gate dielectric layer. The influence of a conventional photolithography process upon the dielectric layer is analyzed regarding electrical instabilities in the device characteristics. The impact of an implemented sacrificial layer to reduce chemical stress to the insulating film during photolithography is evaluated. Furthermore, first inverter circuits were integrated and electrically characterized. Additionally, the implementation of this sacrificial layer can be used for future complementary circuit design.

Enzyme mediated autodeposition of protein particles on nanosphere lithographically nanostructured surfaces - Brassat, Katharina; Rüdiger, Arne; Bürger, Julius; Bremser, W.; Strube, Oliver; Lindner, Jörg

Arrangement of perovskitic semiconductor nanoparticles using soft lithography - Brassat, Katharina; Bürger, Julius; Reinecke, Melanie; Briese, Dennis; Duschik, K.; Schaper, Mirko; Lindner, Jörg

Site-selective protein immobilization on regular antidot patterns fabricated by nanosphere lithography - Brassat, Katharina; Rüdiger, Arne; Bürger, Julius; Bremser, W.; Strube, O.; Lindner, Jörg

Hierarchically ordered nanopore structures formed by combined nanosphere and block copolymer lithography - Brassat, Katharina; Kool, Daniel; Lindner, Jörg

Sub-20 nm surface patterning by block copolymer lithography - Brassat, Katharina; Lindner, Jörg

Fabricating metasurface-based optical devices with a low-cost technique - Brodehl, Christoph; Greulich-Weber, Siegmund; Lindner, Jörg

High-resolution TEM and STEM-EELS studies of colloidal Au nanoparticles self-assembled in nanometric SiO2 nanopore arrays fabricated by block-copolymer lithography - Puglisi, R.A.; Bongiorno, C.; Brassat, Katharina; Garozzo, Christina; La Magna, A.; Lindner, Jörg

Automated SEM image analysis of the opening size distribution of nanosphere lithography masks and their origins - Riedl, Thomas; Lindner, Jörg

Theoretical analysis of strain and misfit dislocation stability in axial-heteroepitaxial GaAs/InAs nanopillars - Riedl, Thomas; Lindner, Jörg

Stability of misfit dislocations in axial-heteroepitaxial 3CSiC/c-GaN nanopillars and nanomesas - Riedl, Thomas; Kemper, R.M.; As, Donald; Lindner, Jörg

Enhancement of the critical thickness of CdSe/ZnSe quantum wells via the strain compensation technique - Rieger, T.; Riedl, Thomas; Lindner, Jörg; Pawlis, A.

Cubic GaN on pre-patterned 3C-SiC/Si (001) substrates - As, Donald; Kemper, R.M.; Riedl, Thomas; Lindner, Jörg

Hierarchical self-assembly by colloidal and block copolymer lithography - Brassat, Katharina

Nanopatterning of surfaces with nanosphere lithography, block copolymer lithography and combinations of both - Brassat, Katharina; Brodehl, Christoph; Lindner, Jörg

All-optical tailoring of single-photon spectra in a quantum-dot microcavity system - Breddermann, D.; Heinze, D.; Binder, R.; Zrenner, Artur; Schumacher, Stefan (Physical Review B)
Semiconductor quantum-dot cavity systems are promising sources for solid-state-based on-demand generation of single photons for quantum communication. Commonly, the spectral characteristics of the emitted single photon are fixed by system properties such as electronic transition energies and spectral properties of the cavity. In the present work we study cavity-enhanced single-photon generation from the quantum-dot biexciton through a partly stimulated nondegenerate two-photon emission. We show that frequency and linewidth of the single photon can be fully controlled by the stimulating laser pulse, ultimately allowing for efficient all-optical spectral shaping of the single photon.

Coherent photocurrent spectroscopy of single InP-based quantum dots in the telecom band at 1.5 µm - Gordon, S.; Yacob, M.; Reithmaier, J. P.; Benyoucef, M.; Zrenner, Artur (Applied Physics B)
In this work we study the resonant and coherent properties of single InP-based InAs quantum dots, which show an optical emission in the telecom C-band and L-band. High-resolution resonant photocurrent spectroscopy on p–i–n devices reveals narrow linewidths and fully resolved fine structure splittings. We observe Lorentzian line shapes, which allow for the extraction of dephasing times as a function of the applied bias voltage. Coherent ps laser excitation results in pronounced Rabi rotations with increasing pulse area. For π-pulse excitation, we obtain more than 93 % of the theoretically expected photocurrent amplitude. Our results also demonstrate that such state-of-the-art InP-based quantum dots for the telecom band exhibit promising key parameters comparable to well-established InAs/GaAs counterparts.
Keywords: Bias Voltage; Optical Parametric Oscillator; Molecular Beam Epitaxy Growth; Internal Electric Field; Dephasing Time

How do different Sources of the Variance of Online Consumer Ratings matter? - Zimmermann, Steffen; Herrmann, Philipp; Kundisch, Dennis; Nault, Barrie (Workshop on IS Design and Economic Behavior (ISDEB))

Hemmt die Veräußerungsgewinnbesteuerung unternehmerische Flexibilität? - Hegemann, Annika

Investitionszeitpunktentscheidungen bei Veräußerungsgewinnbesteuerung - Hegemann, Annika

Interest Barrier and Capital Structure Response - Alberternst, Stephan; Sureth-Sloane, Caren
The Organisation for Economic Co-Operation and Development (OECD) recently proposed an interest barrier to fight tax base erosion and profit shifting (BEPS). We use the introduction of such an interest deductibility restriction in Germany as a quasi-experiment and find significant corporate capital structure responses. Using single entity financial statements and a detailed matching approach, we find evidence that companies that are affected by the interest barrier reduce their leverage by 4.7 percentage points more than non-affected companies. The effects are stronger among non-financially constrained firms. Our results imply that interest barrier effects on capital structure have so far been heavily underestimated.

Relevanz der deutschen Zinsschranke für Einzelunternehmer und Personengesellschaften - eine dynamische Analyse der Betroffenheit - Alberternst, Stephan

Die deutsche Zinsschranke : Betroffenheit, Wirksamkeit und ökonomische Konsequenzen - Alberternst, Stephan

Die parametrische und semiparametrische Analyse von Finanzzeitreihen: neue Methoden, Modelle und Anwendungsm\"oglichkeiten - Peitz, Christian

Erfolgsfaktoren bei Mergers and Acquisitions – Warum schaffen Portfoliomaster mehr Value Added? - Sievers, Sönke; Mehring, Oliver; Keienburg, Georg; Kengelbach, Jens (Corporate Finance (VHB-JOURQUAL 3 Ranking D))
Unternehmen, die regelmäßig ihr Geschäftsfeldportfolio durch aktives M&A-Geschäft in Form von Verkäufen und Käufen steuern, erzielen deutlich bessere Ein- und Zweijahresrenditen für Aktionäre als alternative M&A-Strategien. Ursächlich hierfür ist u.a., dass die bekannten Effekte in Form von Abschlägen für z.B. diversifizierende Transaktionen oder Stock-Deals deutlich geringer ausfallen als bei Vergleichsgruppen wie z.B. One-Time-Deal Unternehmen. Dieser Beitrag analysiert die Gründe für den Erfolg von Portfoliomastern, Unternehmen die mehr als vier Deals in fünf Jahren durchführen. Durch ein professionalisiertes M&A-Management grenzen sie sich positiv in ihrer mittel- und langfristigen Renditeentwicklung gegenüber Strategic-Shiftern (zwei bis vier Deals) und One-Timern ab. Ihr Erfolg beruht darauf sowohl bei diversifizierenden als auch Stock-Deals bekannte übliche Performanceabschläge zu vermeiden und auch in volatilen Markphasen wertschaffende Deals umzusetzen.
Keywords: M&A; Erfolgsfaktoren; Transaktionsanzahl; Diversifizierung; Volatilität; Cash-Deals; Stock-Deals; Portfoliomaster

Wealth effects of rare earth prices and China’s rare earth elements policy - Müller, Maximilian; Schweizer, Denis; Seiler, Volker (Journal of business ethics)

Shadows of the past: The effect of communist heritage on employee consultation - Oertel, Simon; Thommes, Kirsten; Walgenbach, Peter (ILR Review)

Organizational Failure in the Aftermath of Institutional Upheaval - Thommes, Kirsten; Oertel, Simon; Walgenbach, Peter (Organization Studies)

Masters of the Corporate Portfolio - Kengelbach, Jens; Keienburg, Georg; Schmid, Timo; Sievers, Sönke; Mehring, Oliver

Boomerang: Demand-Driven Flow- and Context-Sensitive Pointer Analysis for Java - Späth, Johannes; Nguyen Quang Do, Lisa; Ali, Karim; Bodden, Eric (European Conference on Object-Oriented Programming (ECOOP))
Keywords: ATTRACT; ITSECWEBSITE